Respuesta :

Answer:

7, 4, 1, and -2.

Step-by-step explanation:

Our recursive rule is:

[tex]f(1)=7\!, f(n)=f(n-1)-3[/tex]

Where n is the nth term.

So, our first term will be f(1). As defined, this is 7.

Our second term will be f(2). We will use the recursive formula. Substituting 2 for n yields:

[tex]f(2)=f(2-1)-3[/tex]

Subtract:

[tex]f(2)=f(1)-3[/tex]

We know that f(1) is 7. Substitute:

[tex]f(2)=7-3=4[/tex]

Hence, the second term is 4.

We will do the same thing for the third term. Substitute 3 for n:

[tex]f(3)=f(3-1)-3[/tex]

Subtracting yields:

[tex]f(3)=f(2)-3[/tex]

We know that f(2) is 4. So:

[tex]f(3)=4-3=1[/tex]

Hence, the third term is 1.

Finally, we will do the same thing. Substitute 4 for n to find the fourth term:

[tex]\begin{aligned} f(4)&=f(4-1)-3 \\ f(4)&=f(3)-3 \\ f(4)&=1-3 \\ f(4)&=-2\end{aligned}[/tex]

Hence, the fourth term is -2.

Therefore, our first four terms are 7, 4, 1, and -2.